Edukasi Internet Ramah Anak dan Keluarga pada Masa Pandemi COVID-19 di Desa Cibanteng, Jawa Barat - Riany, Yulina Eva; Rahmawati, Laeli; Farhan, Muhammad; Napitupulu, Princilya Anggraeni; Azzahra, Devita Fatimah; Anggini, Awanda Wira; Raditya, Vincentius Yolanda Angger; Tobing, Yolanda Dheva Lumban; Anastasya, Setia; Evafroditus, Yuniarta (Institut Pertanian Bogor, 2023)
The Covid-19 pandemic has changed various social activities, including family life. Due to the implementation of Community Activity Restrictions (PPKM) within society, social activities have many limitations, including school activities that have been conducted through online learning. This condition leads to an increase in internet use among children. This community service activity aims to educate parents regarding strategies to guide their children in using the internet appropriately. This activity was carried out in Cibanteng Village, Ciampea District, Bogor, West Java, using a structured online socialization and discussion method among 59 parents with school-age children. Results indicated an increase in the participants' knowledge, particularly related to the benefits of the internet for children in learning. Participants' knowledge regarding appropriate strategies for assisting children in using the internet, monitoring strategies, and using the internet appropriately also increased after participating in structured socialization, which was conducted online. The results indicated the need to implement other programs on a larger scale for parents.